The Victorian Woman Question in Contemporary Feminist Fiction - King, J. author. aut Link
IX, 210 p.
Keywords: The Victorian Woman Question in Contemporary Feminist Fiction explores the representation of Victorian womanhood in the work of some of today's most important British and North American novelists including A.S. Byatt, Sarah Waters, Margaret Atwood, Angela Carter and Toni Morrison. By analysing these novels in the context of the scientific, religious and literary discourses that shaped Victorian ideas about gender, it contributes to an important inter-disciplinary debate. For while showing the power of these discourses to shape women's roles, the novels also suggest how individual women might challenge that power through their own lives.